Navigating monkeypox: Identifying risks and implementing solutions - Suhita Aryaloka; Aswin Rafif Khairullah; Muhammad Khaliim Jati Kusala; Ima Fauziah; Nanik Hidayatik; Muhammad Agil; M. Gandul Atik Yuliani; Arindita Niatazya Novianti; Ikechukwu Benjamin Moses; Muhammad Thohawi Elziyad Purnama; Syahputra Wibowo; Kartika Afrida Fauzia; et al. (Open Veterinary Journal)
Monkeypox is a zoonotic disease caused by the orthopox virus, a double-stranded DNA virus which belongs the Poxviridae virus family. It is known to infect both animals (especially monkeys and rodents) and humans and causes a rash similar to smallpox. Humans can become infected with monkeypox virus (MPXV) when they get in close contact with infected animals (zoonotic transmission) or other infected people (human-human transmission) through their body fluids such as mucus, saliva, or even skin sores. Frequently observed symptoms of this disease include fever, headaches, muscle aches, and a rash that initially looks like a tiny bump before becoming a lump that is filled with fluid. Monkeypox symptoms also include an incubation period of 5-21 days, divided into prodromal and eruption phases. Several contributing factors, such as smallpox vaccine discontinuation, widespread intake of infected animal products as a source of protein, high population density, amongst others, have been linked to an increase in the frequency of monkeypox outbreaks. The best course of action for diagnosing individuals who may be suffering with active monkeypox is to collect a sample of skin from the lesion and perform PCR molecular testing. Monkeypox does not presently have a specific therapy; however, supportive care can assist in managing symptoms, such as medication to lower body temperature and pain. Three major orthopoxvirus vaccines have been approved to serve as a preventive measure against monkeypox: LC16, JYNNEOS, and ACAM2000. The discovery that the monkeypox outbreak is communicable both among humans and within a population has sparked new public health worries on the possibility of the outbreak of another viral pandemic. Research and studies are still being conducted in order to gain a deeper understanding of this zoonotic viral disease. This review is therefore focused on deciphering monkeypox, its etiology, pathogenesis, transmission, risk factors, and control. [Open Vet J 2024; 14(12.000): 3144-3163]